Contemporary topics in undergraduate experimental organic chemistry - OER project materials - Piyaratne, Panduka, author (Colorado State University. Libraries, 2023)
A supplementary OER booklet for Undergraduate Organic Chemistry Laboratory Courses offered by the Department of Chemistry, Colorado State University.

Please, download the file to view "alt text" information.
This document contains a set of materials collected for the OER project funded by the Colorado OER Council Grant (AY 2023).
First edition: May 2023.
Keywords: Open educational resources